2021
DOI: 10.1155/2021/9422417
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Computer Simulation Analysis in Green City Garden Plant Landscape Design

Abstract: As an important component of urban landscape elements, garden plants have the role of improving urban ecological environment and forming landscape effects. Digital landscape is a high-simulation model of the system combined with computer hardware and software systems, which allow analysis of the application of computer simulation in the analysis of the value of urban landscape design. In this paper, we propose a “Task-Crowd-Process-Evaluation” computer simulation analysis framework to support management decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The use of digital technology to assist in the study of the composition of landscape spaces is an inevitable trend in the context of social demand, disciplinary development, and technological innovation. From the perspective of social demand, the composition of space research helps to improve the quality of urban green space to meet people's demand for high-quality urban space [1]. From the view of the discipline itself, the change in design concepts determines that the scientific and quantitative perspective of the landscape garden space research is consistent with the development trend of the discipline [2].…”
Section: Introductionmentioning
confidence: 99%
“…The use of digital technology to assist in the study of the composition of landscape spaces is an inevitable trend in the context of social demand, disciplinary development, and technological innovation. From the perspective of social demand, the composition of space research helps to improve the quality of urban green space to meet people's demand for high-quality urban space [1]. From the view of the discipline itself, the change in design concepts determines that the scientific and quantitative perspective of the landscape garden space research is consistent with the development trend of the discipline [2].…”
Section: Introductionmentioning
confidence: 99%
“…Literature [17] used the method of joint analysis to compare the differences in landscape element preferences between the public and experts and proposed a comprehensive ranking combination of landscape element preferences, which provided new ideas for urban landscape design. Literature [18] incorporates garden plants into the urban landscape design space, proposes a digital landscape design model based on computer simulation, and enhances the landscape planning effect based on automated data design. Literature [19] proposed an intelligent approach to landscape design and land planning by combining neural networks and wireless sensors, using digital technology to continuously explore the best parameters for urban landscape design.…”
Section: Introductionmentioning
confidence: 99%
“…Literature [23] showed that digital technology has a positive impact on urban landscape design, and by analyzing intelligent landscape design and land planning based on neural networks and wireless sensor networks, the authors concluded that parametric design is indispensable in modern urban landscapes. Literature [24] analyzes the role of landscape plants in urban landscapes by proposing a computer simulation analysis framework for "task-crowd process evaluation".…”
Section: Introductionmentioning
confidence: 99%